DataQI.NET: A Framework for Specifying Query Criteria Using the Repository Pattern - Carneiro, Carlos Henrique Gouveia; Maia, Paulo Henrique M. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
During the construction of applications that require integration with databases, developers often dedicate a considerable amount of time writing the data access layer. Although there are some tools that aim at improving that process, it still demands a great amount of (usually default) code, which is error-prone, takes effort and time from the developer, and reduces the code reuse potential. This paper presents the DataQI.NET, a framework that encapsulates the complexity of those tools and makes possible the definition of customized queries through method signatures on interfaces that follow the Repository Pattern, allowing the developer to focus more on the business rules implementation. A comparative study is provided considering the implementation with and without the framework, demonstrating that, by using DataQI.NET, we obtain more homogeneous and standardized query methods that communicate, supporting code reuse and significant reduction on the lines of code and implementation time.